Becoming “Teacher”: A Narrative Journey from Undergraduate Education Student to University Instructor - Lucas Skelton (Canadian Journal for New Scholars in Education, 2023)
Similar to their counterparts in K-12 education, novice university instructors often confront a unique set of challenges when teaching at the post-secondary level for the first time. This article narrates the formative experiences of a novice university instructor who also teaches English as an Additional Language (EAL). By sharing insights from my experience as an undergraduate education student, my work with EAL adults, and my first term as a university sessional instructor, this paper provides valuable lessons and reflections that emerging university educators can resonate with and learn from.